A new species of Entomobrya (Collembola: Entomobryidae) from the Northeast China and first record of Entomobryoides sotoadamesi - Chang, Yan; Pan, Zhixiang; Ma, Yitong (Zootaxa, 2020)
A new species of Entomobrya Rondani: E. tristriata sp. nov., from Jilin, one province of the Northeast China and first record of Entomobryoides sotoadamesi Jordana, Potapov & Baquero, 2011, are herein described. Entomobrya tristriata sp. nov. is characterised by three longitudinal dark blue stripes from Th. II to Abd. III, prelabral smooth chaetae and larger subapical tooth on mucro. However, in most species of Entomobrya, prelabral chaetae are ciliated and subapical tooth is subequal to the apical one. Entomobryoides sotoadamesi was first described from Far East of Russia and Chinese specimens agree with the original description.